2005
DOI: 10.1111/j.1478-3231.2005.01091.x
|View full text |Cite
|
Sign up to set email alerts
|

Outcome from molecular adsorbent recycling system (MARS) liver dialysis following drug‐induced liver failure

Abstract: MARS liver dialysis in a setting without timely liver transplantation is associated with a poor outcome. It does, however, provide a window of time for consideration of living donors in the setting of limited cadaveric donors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 32 publications
1
22
0
Order By: Relevance
“…The fact that these patients were, therefore, in better clinical condition prior to LTX might contribute to the high overall survival of transplanted patients. The favorable effect of MARS treatment on laboratory parameters, as we observed, has also been reported in many small, uncontrolled studies [26,27,[37][38][39][40][41][42][43][44] . However, the improvement in laboratory values alone might be only temporary and does not necessarily predict a favorable outcome.…”
Section: Discussionsupporting
confidence: 65%
“…The fact that these patients were, therefore, in better clinical condition prior to LTX might contribute to the high overall survival of transplanted patients. The favorable effect of MARS treatment on laboratory parameters, as we observed, has also been reported in many small, uncontrolled studies [26,27,[37][38][39][40][41][42][43][44] . However, the improvement in laboratory values alone might be only temporary and does not necessarily predict a favorable outcome.…”
Section: Discussionsupporting
confidence: 65%
“…Hepatotoxic drugs and herbal indigenous medicines are important causes for liver failure in the Asia-Pacific region [25,26].…”
Section: Definition Of Aclfmentioning
confidence: 99%
“…It was suggested that MARS may be of particular benefit in some specific causes of acute live failure (eg, Wilson's disease and Amanita phalloides poisoning) [44,45]. In a series of 13 patients who had drug-induced acute liver failure treated with MARS, however, the mortality rate was 85% [46].…”
Section: Liver Support Devicesmentioning
confidence: 99%